Pengaruh Latihan Skiping terhadap Keterampilan Lompat Jauh pada Siswa Sekolah Menengah Atas: Sebuah Studi Eksperimental - Handika Prayoga Putra (Joska: Jurnal Isori Kampar, 2024)
This study investigated the impact of structured skipping training on long jump performance in high school students. Sixty students (ages 15—17, balanced by gender) were randomly assigned to experimental and control groups. The experimental group engaged in an 8-week skipping program, while the control group maintained their usual activities. Long jump performance was assessed pre- and post-intervention using standardized IAAF tests. Data analysis indicated a significant enhancement in the experimental group's long jump skills compared to controls (p<0.001, partial η²=0.425). The experimental group exhibited a mean jump distance increase of 0.37 m (8.7%), whereas the control group showed a mere 0.04 m (0.9%) increase. These findings suggest that skipping exercises effectively enhance long jump skills in high school students, with implications for physical education and athletic training curricula.